Study on Color Properties of Auricularia auricula-judae (Bull.) Quél. Affected by Nano Edible Coatings, Packaging Types, and Storage Temperatures - Kusumiyati, Kusumiyati; Rachman, Aulia Afifah; Hamdani, Jajang Sauman (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Wood ear mushroom is a traditional edible and medicinal mushroom widely consumed as a food supplement. The color of the fruit body is a crucial indicator of commercial quality that influences consumer purchasing interest. However, color quality can decrease due to inappropriate post-harvest technology. The application of nano edible coating, packaging, and storage temperature can help maintain color stability during storage. This study aims to determine the effect of nano edible coating, packaging, and storage temperature on the color of wood ear mushrooms based on the parameters L*, a*, b*, Chroma, Hue, Browning Index, and color difference. The experimental design used was a Completely Randomized Design (CRD) with a combination of nano edible coating (sodium alginate and aloe vera), packaging (biodegradable, wrap, and vacuum plastic), and storage temperatures (±25 ℃, 10 ℃, and 5 ℃). Each treatment was repeated twice, resulting in 38 experimental units, each consisting of 3 mushrooms, total of 114 mushrooms. The results showed that nano aloe vera with vacuum packaging at a storage temperature of 5 ℃ provided the best results in maintaining the color of the wood ear mushroom during storage, with the lowest lightness and color difference values.